Students’ Reactions Toward the Use of An AI-Powered Website for Learning Cardiovascular Biology - Babalola, Ebenezer Omolafe; Olumorin, Charles Olubode; Omolafe, Eyiyemi Veronica (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Artificial Intelligence-powered websites (AI-PW) leverage artificial intelligence to deliver personalised and adaptive learning experiences, enhancing engagement and accessibility. Despite their potentials, there is a shortage of empirically validated-AI resources for learning Cardiovascular Biology (CVB) in Nigeria. This study investigated students’ reactions toward the use of an AI-powered website for learning CVB in Nigeria. The study adopted a research design involving undergraduates from two purposively selected universities in Ilorin metropolis. A total of 68 students participated in the study. Data were collected using the Students’ Reaction Questionnaire (SRQ), which demonstrated a high reliability coefficient of 0.94. Descriptive statistics and t-tests were employed to analyze the data at a 0.05 level of significance. Findings revealed that students’ reactions toward the use of the AI-powered website for learning CVB were positive (x = 2.86 > 2.50). Furthermore, there was no significant difference in students’ reactions toward the use of the developed AI-powered website for learning CVB based on gender. The study concluded that the use of the BeeNCardiac AI-powered website positively influenced students’ learning experiences in cardiovascular biology. It is therefore recommended that students be encouraged to use the BeeNCardiac AI-powered website as a complementary tool for learning CVB in Nigerian universities.